2022
DOI: 10.3389/fpubh.2022.851714
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mortality and Inflation in China: Based on the Mixed Frequency VAR Analyses

Abstract: Reducing neonatal mortality is an important goal in the Sustainable Development Goals (SDGs), and with the outbreak of the new crown epidemic and severe global inflation, it is extremely important to explore the relationship between inflation and infant mortality. This paper investigates the causal relationship between inflation and infant mortality using a mixed frequency vector autoregressive model (MF-VAR) without any filtering procedure, along with impulse response analysis and forecast misspecification va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…IMR varies widely across different states and socioeconomic groups [ 25 ]. A study in China analyzing the IMR from 1999 to 2019 suggested that inflation has an impact on infant mortality [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…IMR varies widely across different states and socioeconomic groups [ 25 ]. A study in China analyzing the IMR from 1999 to 2019 suggested that inflation has an impact on infant mortality [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these green innovation activities tend to mitigate environmental pollution and promote public health ( 12 ). China is still a developing country with low per capita income, and the number of deaths remains relatively high ( 13 , 14 ). Environmental pollution, ecological environment damage, and other problems seriously threaten the health of Chinese residents ( 15 ).…”
Section: Introductionmentioning
confidence: 99%